PENERAPAN METODE CUSTOMER SATISFACTION INDEX (CSI) dan SERVICE QUALITY DALAM MENENTUKAN TINGKAT KUALITAS PELAYANAN TERHADAP KEPUASAN CUSTOMER WEDDING ORGANIZER - mustaqim mustaqim (Ekliptika, 2023)
customer satisfaction process relates to the quality of service products in the CV. X company. More and more customers are on a CV. X then the company is required to provide a quality service to increase customer satisfaction, of course, a method is needed to analyze the level of customer satisfaction. This study aims to determine the value of the customer satisfaction index and service quality on a CV. X to improve the level of service quality according to the will of consumers. The results of this study include providing a customer satisfaction index and service quality value of 74%. In the five dimensions of tangible, reliability, responsiveness, assurance, and empathy, all these dimensions have negative gap values (-). The average tangible gap is 0.608; the staff was very quick in setting up the facility (-0.23); quick and easy ordering process (-0.20); and the staff is very responsive in taking care of all the needs of the guests (-0.17) with an average gap of -0.597 then the responsiveness of the attribute statement is that the WO team can reprimand the mistakes of the guests (-0.20), the WO team can accept criticism from the customer (-0.23), the WO team serves wholeheartedly so that the customer feels commensurate with the price paid (-0.06).